Dried blood spots for anti‐doping: Why just going volumetric may not be sufficient. Issue 1 (22nd November 2020) - Luginbühl, Marc; Gaugler, Stefan
Abstract : The perspective discusses quantitative DBS analysis for anti‐doping testing in an athletic population and why only using volumetric sampling for this subgroup might not be enough. It presents examples to highlight where HCT variations occur, followed by a whole blood to plasma ratio and an HCT extraction bias discussion. Finally, options to correct for the HCT bias are presented.